2003
DOI: 10.1167/iovs.02-0159
|View full text |Cite
|
Sign up to set email alerts
|

Monosomy 3 in Uveal Melanoma: Correlation with Clinical and Histologic Predictors of Survival

Abstract: Monosomy 3 correlates with survival but can be predicted only in patients with large epithelioid tumors. The absence of monosomy 3 is predictable only in patients who have small, spindle-cell tumors. In most patients, prediction of monosomy 3 according to tumor size and histology is unreliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
4
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(164 citation statements)
references
References 10 publications
5
152
4
3
Order By: Relevance
“…In our study, monosomy 3 was detected in 38% of the epithelioid/mixed cell types (Table 5). This was not shown to be statistically significant by Fisher exact test, differing from the results of others 16,17,23 who reported a strong correlation between monosomy 3 and epithelioid/mixed cell types. The CISH assay detected monosomy 3 in 29% of the 48 cases (epithelioid, mixed, and spindle cell types) in this study.…”
Section: Commentcontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, monosomy 3 was detected in 38% of the epithelioid/mixed cell types (Table 5). This was not shown to be statistically significant by Fisher exact test, differing from the results of others 16,17,23 who reported a strong correlation between monosomy 3 and epithelioid/mixed cell types. The CISH assay detected monosomy 3 in 29% of the 48 cases (epithelioid, mixed, and spindle cell types) in this study.…”
Section: Commentcontrasting
confidence: 99%
“…Both monosomy 3 analysis using the microsatellite DNA assay and transcriptome profiling have been successfully performed in fine-needle biopsy uveal melanoma specimens taken prior to radiotherapy, and CISH has been shown to work successfully on fine-needle biopsies from breast and lung cancer patients. [28][29][30][31] Previous studies 16,17,23 have shown epithelioid cells to correlate with loss of 1 copy of chromosome 3. In our study, monosomy 3 was detected in 38% of the epithelioid/mixed cell types (Table 5).…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting a little over a decade ago, investigators around the world began to report that chromosomal and transcriptional features of primary uveal melanoma cells were strongly associated with the pa tient's likelihood of developing subsequent extraophthalmic metastasis and metastatic death (25,(29)(30)(31)(32)(33)(34)(35) Several authors have shown that these chromosomal and transcriptional features can be determined on tumor specimens obtained by FNAB changing the indication for FNAB from purely diagnostic to investigational-prognostic (24,25,(36)(37)(38) . During the past few years, investigators from several of these centers have reported their experience with cytogenetic testing of the obtained FNAB aspirates (25,27,35,37,(39)(40)(41) .…”
Section: Prognostic Implications Of Cytopathologic Classification Of mentioning
confidence: 99%
“…12,13 The histological detection of looping vasculogenic mimicry patterns has been associated with an aggressive clinical course in multiple independent studies. [14][15][16][17][18][19] The presence of these patterns is associated with monosomy 3 20 (a cytogenetic marker of aggressive uveal melanoma behavior 20,21 ) and a gene expression signature that is associated with the development of metastatic uveal melanoma. 22 The clinical detection of these patterns by confocal ICG angiography has been associated with the eventual growth of small and indeterminate posterior choroidal melanocytic lesions.…”
Section: Introductionmentioning
confidence: 99%